Dynamic Testing of Reinforced Glass Fibre-Epoxy Composite at Elevated Temperatures - Gieleta, R.; Kruszka, L. (Проблемы прочности, 2002)
We present the experimental analysis of the deformation, strength and failure of tubular speciImens, made of woven reinforced glass fibre-epoxy composite. These specimens were subjected to uniaxial tensile testing with the average strain rates of about 10 ^-5 and up to 20 с ^-1 . Tests were performed at room and three elevated temperatures, up to the temperature corresponding to the phase change of the matrix. Проведено експериментальний аналіз деформування, міцності і руйнування трубчастих зразків, виготовлених із армованого скловолокном епоксидного композита. Зразки випробовували на одновісний розтяг при середній швидкості деформації від 10 ^-5 до 20 c ^-1. Випробування проводили за кімнатної температури, а також за трьох підвищених до моменту фазового перетворення матриці. Представлен экспериментальный анализ деформирования, прочности и разрушения трубчатых образцов, изготовленных из армированного стекловолокном эпоксидного композита. Образцы подвергались одноосному растяжению при средних скоростях деформации от 10^-5 до 20 с^-1. Испытания проводились при комнатной температуре, а также при трех повышенных температурах до момента фазового превращения матрицы.